The Effectiveness Of Telemedicine To Improve Quality Of Life For Patients In The COVID-19 Pandemic - Nutrisia Aquariushinta Sayuti; Nur - Atikah (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: COVID-19 delivers the effects of health services in form. Health services began to enforce health protocols, especially social distancing. Medical consultations carried out during medical visits become remote medical consultations by maximizing electronic health technology (e-health), telehealth, and/or telemedicine. The use of health technology has increased research on telemedicine’s effectiveness on patients' health-related quality of life (HRQoL). The aim of this study is to analyze the effectiveness of telemedicine in improving the quality of life of chronic disease patients that require regular visits to health providers during the COVID-19 pandemic during Covid-19 Pandemic. Methods: The research was descriptive. A systematic review with source data from Pubmed, ScienceDirect, and Sage databases with the keyword "COVID-19 and telemedicine and health-related quality of life". Criteria were limited to all clinical study articles published during the COVID-19 pandemic in Indonesian or English and published during the COVID-19 pandemic. Results: Eleven (11) articles were successfully selected. Telemedicine was used for kidney transplantation or minor stroke patients, amyotrophic lateral sclerosis (ALS), cancer, adrenal insufficiency, chronic obstructive pulmonary disease (COPD), and primary antibody deficiency patients. The instruments used to measure HRQoL were generic (the EQ-5D and SF-36) and specific for some diseases. The results showed that telemedicine could maintain HRQoL and reduce depression or anxiety. Conclusion: Telemedicine is a feasible and effective intervention to maintain HRQoL and reduce the consequences of social distancing during the COVID-19 pandemic. The recommendation is telemedicine must continue to be developed in health services even though the COVID-19 pandemic is over.